Gestão de bibliotecas na Universidade Federal da Paraíba: análise com base nos indicadores de avaliação - Maia, Mara Leurany Jorge (2021)
This work aimed to analyze the management of libraries at the Federal University of Paraíba (UFPB) based on the evaluation of indicators of the National Institute of Educational Studies and Research Anísio Teixeira (INEP), the International Organization for Standardization (ISO) 11620 (2014) and the International Federation of Library Associations and Institutions (IFLA). The theoretical framework is based on the themes of university libraries and the National System of Higher Education Assessments (SINAES), analyzed here, mainly in the light of studies: Cunha (2000, 2008 and 2016) about assessment in libraries and Dias Sobrinho (2000 and 2003) on institutional assessment of higher education. Also part of the theoretical framework of this research are the legislation relating to SINAES and other documents of the Ministry of Education (MEC), as well as the assessment standards of the International Organization for Standardization and the International Federation of Library Associations and Institutions on assessment in university libraries. The research has a descriptive, exploratory and qualitative nature, to answer how the management of libraries at the Federal University of Paraíba works, based on indicators from INEP/MEC, ISO 11620 (2014) and IFLA. Guided by this purpose, the research carried out, through a bibliographic and documental study, a qualitative and content analysis. Its data source was the official documents of institutional evaluations, the Institutional Development Plan 2019-2023 and the 2020 Self-Assessment for evaluating the UFPB libraries, which were compared and interpreted. We conclude that when evaluated in light of the assessment guidelines of ISO 11620 (2014) and IFLA, it suggests a gap between such indicators and the INEP/MEC instruments and also the institutional ones. Finally, we emphasize the need for a specific assessment in order to diagnose and support management decision-making, in the process of continuous improvement and the constant need for technological updates imposed by a digital society. We also present, as a contribution, a set of quality indicators able to support the evaluation processes in libraries.